Pengaruh Model Problem Based Learning terhadap Keterampilan Geografi - Fiqih Ainal Farah; Budi Handoyo; Syamsul Bachri (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: The purpose of this research is to determine the effect of the Problem Based Learning model on geography skills. The subjects of this research were X.4 as the control class, and X.5 as the experimental class in MAN Kota Batu. This research used Quasy Experiment method with nonequivalent design (pretest and posttest) control group. The hypothesis test result by using Two Way Anova. The result was significance value of 0.014. The conclusion was the Problem Based Learning model significantly influenced the students’ geographical skills.